Association of serum intestinal fatty-acid binding protein, inflammatory and oxidative stress markers with colorectal cancer among Ghanaian patients - Genevieve Kwao-Zigah; Antoinette Bediako-Bowan; Gabriel Atampugre Atampugbire; Caleb Koranteng Kwayisi-Darkwah; Osbourne Quaye; Gloria Kezia Aryee; Emmanuel Ayitey Tagoe (PLoS ONE, 2025)
Background In sub-Saharan Africa, colorectal cancer (CRC) is becoming an increasingly serious public health issue. However, little is known about the relationships between inflammation, oxidative stress, and intestinal barrier biomarkers in African populations. This study examined the association between selected biomarkers, dietary factors, and the risk of CRC among treatment-naïve patients in Ghana. Methods This hospital-based analytical cross-sectional study included twenty-eight CRC patients and twenty-six non-CRC volunteers. Serum samples processed from whole blood were analyzed for tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and intestinal fatty acid binding protein (iFABP) levels using enzyme-linked immunosorbent assays (ELISA). The thiobarbituric acid test was used to measure the concentration of serum malondialdehyde (MDA). Dietary intake data were collected using structured questionnaires. Logistic regression models were used to evaluate associations with CRC risk. Results CRC patients showed significantly higher levels of TNF-α, IL-1β, MDA and iFABP compared to the control group (p < 0.05). A Pearson correlation analysis revealed a significant positive correlation between IL-1β and TNF-α levels (r = 0.606, p < 0.000). TNF-α and MDA levels were significantly associated with increased odds of CRC in both crude and adjusted models (p < 0.05). In contrast, IL-1β and iFABP showed only crude significant associations with CRC. Dietary factors, including alcohol consumption, red/processed meat, vegetables, and dairy intake, were not significantly associated with CRC risk. Conclusion The study identifies TNF-α and MDA as potential biomarkers associated with CRC, emphasizing the role of inflammation and oxidative stress in CRC pathogenesis in Ghana. The lack of adjusted association with iFABP may reflect population-specific patterns or limited statistical power. Further large-scale longitudinal studies are warranted.